The Creation of Musical Folk Drama to "Bang Lamphu Yod Rak" - Phetruchee, Mananshaya (Journal of Cultural Approach, 2022)
This article is a part of a research project on Bang Lamphu community identity : the creation of the "Bang Lamphu Yod Rak" musical folk drama. The author aims to explore how to create musical folk dramas within the Bang Lamphu community and its impact on identity. This research creates and designs the musical folk drama "Bang Lamphu Yod Rak", which synthesizes knowledge from texts, academic documents, practicing, observations, expert interviews, and a review of previous research. The results of the research showed that the creation of the musical folk drama consists of six elements: concepts, actors, lyric design, posture design, costume design and the use of stage design. The musical folk drama on "Bang Lamphu Yod Rak" showed that “Likay” can be adapted to communicate to the audience. The results of this creative research have brought musical folk drama to "Bang Lamphu Yod Rak". This performance can be a model for developing or studying the identity of a community. The musical folk drama guides the awareness of invaluable artistic values into the community culture. This performance was able to present the identity of Bang Lamphu community through performing arts as well as being a magnet to attract Thai and foreign tourists.